Is Prone Position [18F]FDG PET/CT Useful in Reducing Respiratory Motion Artifacts in Evaluating Hepatic Lesions? - Chung Won Lee; Hye Joo Son; Ji Young Woo; Suk Hyun Lee (Diagnostics, 2023)
Prone position is useful in reducing respiratory motion artifacts in lung nodules on 2-Deoxy-2-[18F] fluoro-D-glucose ([18F]FDG) positron emission tomography/computed tomography (PET/CT). However, whether prone position PET/CT is useful in evaluating hepatic lesions is unknown. Thirty-five hepatic lesions from 20 consecutive patients were evaluated. The maximum standardized uptake value (SUVmax) and metabolic tumor volume (MTV) of both standard supine position PET/CT and additional prone position PET/CT were evaluated. No significant difference in SUVmax (4.41 ± 2.0 vs. 4.23 ± 1.83; p = 0.240) and MTV (5.83 ± 6.69 vs. 5.95 ± 6.24; p = 0.672) was observed between supine position PET/CT and prone position PET/CT. However, SUVmax changes in prone position PET/CT varied compared with those in supine position PET/CT (median, −4%; range: −30–71%). Prone position PET/CT was helpful when [18F]FDG uptake of the hepatic lesions was located outside the liver on supine position PET/CT (n = 4, SUVmax change: median 15%; range: 7–71%) and there was more severe blurring on supine position PET/CT (n = 6, SUVmax change: median 11%; range: −3–32%). Unlike in lung nodules, prone position PET/CT is not always useful in evaluating hepatic lesions, but it may be helpful in individual cases such as hepatic dome lesions.